Presence Service in IMS - David Petras; Ivan Baronak; Erik Chromy (The Scientific World Journal)
This paper describes the presence service, which is located in the IP multimedia subsystem. This service allows making many applications for different groups of people. The paper describes differences between a network without the service and with the service. The biggest change is an increased number of transmitted messages. The presence uses some part of the IP multimedia subsystem control layer, which is shown in communication between the user and the server. The paper deals with the number of generated messages depending on the behaviour of the users. This is described by a mathematical model using discrete Markov chains.